Barriers to formal health care seeking during pregnancy, childbirth and postnatal period: a qualitative study in Siaya County in rural Kenya - Caroline A. Ochieng; Aloyce S. Odhiambo (BMC, 2019)
Abstract Background There is broad agreement that antenatal care (ANC) interventions, skilled attendance at birth and management of complications arising after delivery are key strategies that can tackle the high burden of maternal mortality in sub-Saharan Africa. In Kenya, utilisation rate of these services has remained low despite a government policy on free maternal care. The present study sought to understand what factors are leading to the low healthcare seeking during pregnancy, child birth and postnatal period in Siaya County in Kenya. Methods Six Focus Group Discussions were conducted with 50 women attending ANC in 6 public primary healthcare facilities. Participants were drawn from a sample of 200 women who were eligible participants in a Conditional Cash Transfer project aimed at increasing utilization of healthcare services during pregnancy and postnatal period. Interviews were conducted at the health facilities, recorded, transcribed and analysed using thematic analysis. Results Multiple factors beyond the commonly reported distance to health facility and lack of transportation and finances explained the low utilization of services. Emergent themes included a lack of understanding of the role of ANC beyond the treatment of regular ailments. Women with no complicated pregnancies therefore missed or went in late for the visits. A missed health visit contributed to future missed visits, not just for ANC but also for facility delivery and postnatal care. The underlying cause of this relationship was a fear of reprimand from the health staff and denial of care. The negative attitude of the health workers explained the pervasive fear expressed by the participants, as well as being on its own a reason for not making the visits. The effect was not just on the woman with the negative experience, but spiraled and affected the decision of other women and their social networks. Conclusions The complexity of the barriers to healthcare visits implies that narrow focused solutions are unlikely to succeed. Instead, there should broad-based solutions that focus on the entire continuum of maternal care with a special focus on ANC. There is an urgent need to shift the negative attitude of healthcare workers towards their clients.